Design and implementation of crowd sourcing based delivery system - Zidelkhir, Ali; Ben Saad, Mohamed Lahcen (Université Amar Telidji - Laghouat - Département d'informatique, 2021)
The demand for transportation is at an all time high and is continuing to increase with time.We all agree to the importance that transportation holds in maintaining the ﬂow of goods and cash as well as its role in the economy.Crowd sourced delivery is considered a possible solution for complicated problem with on-demand delivery challenge. The purpose of this thesis is to propose the solution of the crowd sourced delivery with regard to service level and quality.The aim of this work is to create a platform that organizes the process of crowd transportation model and helps both drivers and possible clients to better interact. Drivers will be able to save the time, minimise the cost of fuel and avoid the trafc jam. Also have the willing to work at any time.One of the most factors this project will focus on, is the timing and pricing for the clients. using existing method to use in order to solve this problems.The Clients will be able to post their requests that the drivers will handle it in the way of his trip.